Investigation of the dependence of the amplitude of vertical vibration displacements of the working element of a vibrating platform on its inertial and stiffness parameters using a three-factor experiment (Academic journal Industrial Machine Building Civil Engineering, 2024)
During preliminary experimental studies, it was established that the amplitude of vibration displacements of the moving frame points of the vibration platform is most significantly influenced by such characteristics as the stiffness of vibration-isolating supports, the distance from the centre of oscillation, and the mass of the moving part. These factors were selected as independent factors in the research using a three-factor experiment. As a result of mathematical and statistical processing of the experimental data, a second-order multiple regression equation was obtained. The calculated values of the variance at the zero point, the variance of adequacy, and Fisher's criterion confirm the possibility of using the obtained equation to describe the studied process. Based on the research results, three three-dimensional response surfaces were constructed, describing the dependence of the amplitude of vibration displacements of selected points on the surface of the working body of the vibration platform on two variable input factors at a fixed value of the third factor at the base level. The results obtained allow for optimal regulation of vibration-isolating supports with variable stiffness, which, in turn, allows for improving the quality of concrete product compaction.
Keywords: amplitude of vibration displacements; vibration platform; vibration support; stiffness; three-factor experiment